2018
DOI: 10.12688/f1000research.15363.2
|View full text |Cite
|
Sign up to set email alerts
|

Acute hip fracture surgery anaesthetic technique and 30-day mortality in Sweden 2016 and 2017: A retrospective register study

Abstract: Background: Hip fractures affect 1.6 million patients yearly worldwide, often elderly with complex comorbidity. Mortality following surgery for acute hip fracture is high and multifactorial; high age, comorbidities and complication/deterioration in health following surgery. Whether the anaesthesia technique affects the 30-day mortality rate has been studied widely without reaching a consensus. The primary aim of this study was to determine anaesthetic techniques used in Sweden and their impact on the 30-day mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 20 publications
(20 reference statements)
2
20
2
Order By: Relevance
“…First, although hospitals are staffed by highly experienced and educated personnel, the observational design of this study means that we cannot precisely determine to which extent a longer LOS would reduce 30-day mortality, for example in frail men aged 90 and above. Second, we lacked certain covariates of importance, such as an adequate measure of the patient's health status at admission, which may have changed during the study period, as well as data on type of hospital and post-anesthesia care unit LOS, which may influence the 30-day mortality estimates [36,37]. Third, there were some interesting observations with respect to trends in operation techniques, such as a shift toward use of intramedullary nails for intertrochanteric fractures and toward prosthesis for femoral neck fractures.…”
Section: (B) (A)mentioning
confidence: 99%
“…First, although hospitals are staffed by highly experienced and educated personnel, the observational design of this study means that we cannot precisely determine to which extent a longer LOS would reduce 30-day mortality, for example in frail men aged 90 and above. Second, we lacked certain covariates of importance, such as an adequate measure of the patient's health status at admission, which may have changed during the study period, as well as data on type of hospital and post-anesthesia care unit LOS, which may influence the 30-day mortality estimates [36,37]. Third, there were some interesting observations with respect to trends in operation techniques, such as a shift toward use of intramedullary nails for intertrochanteric fractures and toward prosthesis for femoral neck fractures.…”
Section: (B) (A)mentioning
confidence: 99%
“…On univariate analysis, we found that gender had a significant impact on post-op ICU stay as females were less likely to be admitted into ICU despite accounting for a greater number of hip fractures. This is one of the widely reported associations in literature which state that men have higher rates of mortality and morbidity [ [26] , [27] , [28] , [29] , [30] ]. General anesthesia also significantly impacted postoperative ICU admission although this association was not observed on multivariate analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Waesberghe et al performed a meta-analysis and examined the outcomes of general and neuraxial (spinal and epidural) anaesthesia in patients with hip fracture and identified significantly lower rates of in-hospital mortality among the neuraxial anaesthesia group (OR .85, P = .004) but no difference in 30-day mortality rate between patients who received these two types of anaesthesia. 25 Moreover, two other retrospective cohort studies that focused on older adults with hip fracture also reported no difference in 30day mortality rates between these two types of anaesthesia, 26,27 and another study reported that spinal anaesthesia was associated with fewer and less severe adverse effects. 27 In fact, an increased use of spinal anaesthesia over general anaesthesia in older adults with hip fracture has already been observed, which may be attributable to lower interventional morbidity in older patients with frailty.…”
Section: Discussionmentioning
confidence: 99%